High‐Resolution, Highly‐Integrated Traction Force Microscopy Software. Issue 9 (7th September 2021) - Mittal, Nikhil; Han, Sangyoon J.
Abstract: Accurate measurement of cellular traction force is critical for understanding physical interaction between cells and the extracellular matrix. Traction force microscopy (TFM) has become the most widely used tool for this purpose. While TFM has made continual progress in terms of resolution and accuracy, there have been challenges regarding obtaining user‐friendly software and choosing the right values for parameters and sub‐processes associated with the software. Here we provide step‐by‐step instructions for a MATLAB‐based TFM software application equipped with multiple methods for image deformation quantification and force reconstruction, along with clarification on the computational meaning of the parameters within the software. We outline how to choose the optimal sub‐methods and values for parameters for each process, depending on the characteristics of images and purpose of the analyses. The software's runtime is 20, 4, and 0.05 min by Fast BEM L1 (Boundary Element Method L1‐regularization), Fast BEM L2 (L2‐regularization), and FTTC (Fourier Transform Traction Cytometry), respectively, in addition to 7 min of particle‐tracking velocimetry−based deformation tracking, for a single image (1280 × 960 pixel) on a standard workstation. Finally, the colocalization accuracies, in reference to a paxillin‐GFP image, are compared between the three force reconstruction methods. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Setting up the TFM package in MATLAB Basic Protocol 2 : Running the TFM package Alternate Protocol 1 : Stage drift correction: Efficient subpixel registration Alternate Protocol 2 : Force field calculation: FastBEM